Mulakhaṣāt al-Rasā’il al-‘Ilmiyyah (al-Duktūrah) li al-Qism al-Aqīdah wa al-Fikr al-Islāmiyy Ᾱkādīmiyyah al-Dirāsāṭ al-Islāmiyyah bi Jāmi‘ah Malāyā - Muá¹£á¹afa Bahjat, MujÄhid; á¸¤Ämid, Muá¸¥ammad FawzÄ« (Jurnal Usuluddin, 2008)
This article discusses about a number oh Ph.D theses submitted to the Department of Aqidah and Islamic Thought from 1997 to 2007 in five main disciplines of studies , i.e. Aqidah, Ilamic Thought, Sufism, Comparative religion and Islamic Philosophy. The authors in this article explain the content, methodology of research, analysis and findings of the these concerned.